Financial Sector Reform and Economic Development in Nigeria - Babajide, Abiola Ayopo; Ishola, Lawal Adedoyin; Adekunle, Adetiloye Kehinde; Achugamonu, Bede Uzoma; Bosede, Akinjare Victoria (Asian Economic and Financial Review, 2021)
Various reforms have been brought to bear on the financial system ostensibly to improve the country’s macroeconomic variables and the standard of living of the people, among which are the financial reforms that were implemented in recent times. This study examines the impact of financial sector reform on the Human Development Index (HDI) following the recent statistics that show improvement in the HDI of Nigeria since 2005. The study employed several variables as a proxy for financial reforms and adopted the Granger causality test and vector error correction model to analyse the impact of the relationship for the period between 1980 and 2017. The findings revealed a negative long-run relationship between financial sector reform variables and HDI, except for owners’ equity. The study also showed positive short-run dynamics between total savings to GDP and HDI. The study concluded that the recent improvements in HDI, which is the proxy for economic development, are not due to the financial sector’s reforms; rather, some other influences in the economy could be responsible. The study, therefore, recommends a more inclusive reform agenda that will focus on economic development rather than economic growth.